Treatment of Helicobacter pylori infection favourably affects gastric mucosal superoxide dismutases. - Götz, J M (1997)
BACKGROUND AND AIMS: Excessive production of reactive oxygen metabolites (ROMs) by phagocytic cells is thought to contribute to the mucosal pathology of Helicobacter pylori infection. Previously, H pylori infection was shown to have a differential effect on some gastric mucosal scavenger enzymes of ROMs-namely, mitochondrial and cytoplasmic superoxide dismutases-reflected by a large increase in the cytokine inducible manganese superoxide dismutase and a marginal decrease in the constitutive copper/zinc superoxide dismutase. The present study was performed to evaluate whether these altered mucosal superoxide dismutase concentrations and activities in H pylori associated gastritis are reversed to normal by successful treatment of the infection. PATIENTS AND METHODS: In two different treatment groups-namely, omeprazole or ranitidine, in combination with clarithromycin and metronidazole (OME/AB (n = 33) and RAN/AB (n = 30))-manganese superoxide dismutase and copper/zinc superoxide dismutase concentrations were evaluated by enzyme linked immunosorbent assays in homogenates of gastric antrum and corpus biopsy specimens obtained before and eight weeks after successful treatment of H pylori infection. Superoxide dismutase activities in these homogenates were determined spectrophotometrically in eight patients of both groups before and after successful treatment. The concentrations of gastric mucosal superoxide dismutases were also determined in 12 patients with a persistent H pylori infection, with (n = 4) or without (n = 8) eradication therapy. Infection and eradication of H pylori were confirmed by a combination of culture and histology. RESULTS: Concentrations of manganese superoxide dismutase were significantly lower after than before therapy in antral (p < 0.001 in both treatment groups) and corpus (p < 0.001 in both treatment groups) mucosa. By contrast, copper/zinc superoxide dismutase concentrations were significantly higher (p < 0.001) only in antral mucosa of the OME/AB treated group. Manganese superoxide dismutase activity was significantly lower after than before treatment in antral (OME/AB p < 0.01, RAN/AB p < 0.001), but not in corpus mucosa. Copper/zinc superoxide dismutase activity was not significantly altered by therapy. In the 12 patients with a persistent H pylori infection no major changes in the gastric mucosal superoxide dismutase concentrations were found. CONCLUSIONS: The raised manganese superoxide dismutase and reduced copper/ zinc superoxide dismutase concentrations and activities in H pylori associated gastritis were reversed towards normal by successful treatment of the infection.